2015
DOI: 10.1159/000439568
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Epidemiology of Alzheimer's Disease - A Critical Review

Abstract: Background: As adult brain structure is primarily established in early life, genetic and environmental exposures in infancy and childhood influence the risk for Alzheimer disease (AD). In this systematic review, we identified several early life risk factors and discussed the evidence and underlying mechanism for each. Summary: Early risk factors for AD may alter brain anatomy, causing vulnerability to AD-related dementia later in life. In the perinatal period, both genes and learning disabilities have been ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 100 publications
1
69
0
1
Order By: Relevance
“…While Apo E4 is the top gene associated with late onset-AD gene, other genes that may modulate the risk of late-onset AD include CLU, CR1, PICALM, BIN1, SORL1, GAB2, ABCA7, MS4A4/MS4A6E, CD2AP, CD33, APHA1, and HLA-DRB1/5. Other risk factors for AD include head trauma, female gender, learning disabilities, education level, homocysteine levels, socioeconomic status, and previous depression (12). Importantly, vascular risk factors including diabetes and hyperlipidemia are additional risk factors for AD (13,14).…”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…While Apo E4 is the top gene associated with late onset-AD gene, other genes that may modulate the risk of late-onset AD include CLU, CR1, PICALM, BIN1, SORL1, GAB2, ABCA7, MS4A4/MS4A6E, CD2AP, CD33, APHA1, and HLA-DRB1/5. Other risk factors for AD include head trauma, female gender, learning disabilities, education level, homocysteine levels, socioeconomic status, and previous depression (12). Importantly, vascular risk factors including diabetes and hyperlipidemia are additional risk factors for AD (13,14).…”
Section: Etiologymentioning
confidence: 99%
“…At the cellular level, AD is characterized by a progressive loss of cortical neurons most notable in the entorhinal cortex, hippocampus and posterior cingulate cortex (12). The neuronal damage is believed to be related to the deposition of abnormal proteins, which are the hallmark pathological lesions of AD known as the "plaques", found in the extracellular space, and "tangles", inside the cells.…”
Section: Pathophysiology Of Admentioning
confidence: 99%
“…Yet consideration of early-life risk factors in AD is important, as an increasing number of studies suggest that many of the diseases of later life are associated with early-life risk factors. As Seifan et al [2] point out, exposure to adverse childhood events increases the risk of heart disease, stroke and diabetes. Loss of a parent has also been associated with risk of cancer before 40 years of age [5] .…”
mentioning
confidence: 99%
“…Thus, the review of the 'early-life epidemiology' of AD by Seifan et al [2] is welcome. If the factors identified in this review are truly relevant to risk of AD, it may be possible to expand candidates for secondary prevention and even think about 'lifespan primary prevention', that is, interventions designed for entire populations offered early in life.In a careful retrieval and review of nearly 35 years of research, Seifan et al [2] identified 43 papers that examined early-life factors …”
mentioning
confidence: 99%
See 1 more Smart Citation